2019
DOI: 10.5334/gjgl.635
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of at-issue co-speech gestures under contrastive focus

Abstract: The status of content-bearing co-speech gestures, i.e., gestural adjuncts co-occurring with the verbal expressions they adjoin to, has recently become a matter of debate in formal semantics and pragmatics (Ebert & Ebert 2014; Ebert 2017; Tieu et al. 2017; 2018; Esipova 2018; Schlenker 2018; Zlogar & Davidson 2018). The general tendency has been to claim that co-speech gestures by default make not-at-issue contributions, however, the existing analyses differ in whether they in principle allow fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…There are at least two conceivable local interpretations for co-speech gestures. One is that of a restricting modifier (which I will label 'Restricting'), and the other is a hypothetical interpretation corresponding to a locally interpreted NRM inference or a locally interpreted supplement (which I will label 'Non-projecting non-restricting'), as illustrated in (21) Previous experimental studies on gesture projection (Tieu et al 2017(Tieu et al , 2018Esipova 2019) concluded that local interpretations of co-speech gestures are in principle possible, but none of them was designed to distinguish between the two types of local interpretations above. The goal of this study is to do so and to test the relevant predictions of the three theories via an acceptability judgement task.…”
Section: Fitting Gestures Into the Picturementioning
confidence: 99%
“…There are at least two conceivable local interpretations for co-speech gestures. One is that of a restricting modifier (which I will label 'Restricting'), and the other is a hypothetical interpretation corresponding to a locally interpreted NRM inference or a locally interpreted supplement (which I will label 'Non-projecting non-restricting'), as illustrated in (21) Previous experimental studies on gesture projection (Tieu et al 2017(Tieu et al , 2018Esipova 2019) concluded that local interpretations of co-speech gestures are in principle possible, but none of them was designed to distinguish between the two types of local interpretations above. The goal of this study is to do so and to test the relevant predictions of the three theories via an acceptability judgement task.…”
Section: Fitting Gestures Into the Picturementioning
confidence: 99%
“…There is wide agreement that co-speech gesture conveys not-at-issue content (Ebert andEbert 2014, Tieu et al 2018). That is, co-speech gestures tend to project within embedding contexts (Esipova 2019), and cannot be directly denied (Ebert and Ebert 2014). It is less clear whether co-speech gestures can contribute at-issue content, although the emphasis on their not-at-issueness implies not.…”
Section: Approaches To the Body In Spoken Languagementioning
confidence: 99%
“…One potential reason for the variability in acceptability judgements, and perhaps the lower acceptability for utterances with co-speech gestures, is that the above studies use a quite artificial setting. For example, Zlogar and Davidson (2018) and Esipova (2019) use video of a single speaker standing against a plain background using constructed iconic gestures. While this methodology does an excellent job of controlling for other variables, perhaps participants vary in their willingness to accept the artificial construct of the task.…”
Section: Approaches To the Body In Spoken Languagementioning
confidence: 99%
See 2 more Smart Citations